2021
DOI: 10.1111/jgs.17467
|View full text |Cite
|
Sign up to set email alerts
|

National disparities in use of minimally invasive surgery for rectal cancer in older adults

Abstract: BACKGROUND: Minimally invasive surgery (MIS) is safe and improves outcomes in older persons with rectal cancer but may be underutilized. As older persons are the largest surgical population, investigation of the current use and factors impacting MIS use is warranted. Our goal is to investigate the trends and disparities that affect utilization of MIS in older persons with rectal cancer. METHODS: The National Cancer Database was reviewed for persons 65 years and older who underwent curative resection for rectal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
0
12
1
Order By: Relevance
“…Furthermore, non‐Hispanic Black patients are less likely to undergo surveillance or to receive treatment in the forms of radiation or surgery for prostate cancer and have worse outcomes compared to other patients—even after treatment in equitable environments 41 . Though previous research by Kim and colleagues using data from 2006 to 2008 found non‐Hispanic Black patients had decreased odds of undergoing RARP, when evaluating patients who underwent radical prostatectomy in 2010–2017 we found no statistically significant difference in odds of undergoing RARP versus ORP compared to non‐Hispanic White patients in multivariable analysis 42,43 . Even though non‐Hispanic Black patients are less likely to undergo any type of treatment, including surgical treatment, for those who access surgical treatment they are no less likely to receive minimally invasive techniques.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Furthermore, non‐Hispanic Black patients are less likely to undergo surveillance or to receive treatment in the forms of radiation or surgery for prostate cancer and have worse outcomes compared to other patients—even after treatment in equitable environments 41 . Though previous research by Kim and colleagues using data from 2006 to 2008 found non‐Hispanic Black patients had decreased odds of undergoing RARP, when evaluating patients who underwent radical prostatectomy in 2010–2017 we found no statistically significant difference in odds of undergoing RARP versus ORP compared to non‐Hispanic White patients in multivariable analysis 42,43 . Even though non‐Hispanic Black patients are less likely to undergo any type of treatment, including surgical treatment, for those who access surgical treatment they are no less likely to receive minimally invasive techniques.…”
Section: Discussioncontrasting
confidence: 58%
“…41 Though previous research by Kim and colleagues using data from 2006 to 2008 found non-Hispanic Black patients had decreased odds of undergoing RARP, when evaluating patients who underwent radical prostatectomy in 2010-2017 we found no statistically significant difference in odds of undergoing RARP versus ORP compared to non-Hispanic White patients in multivariable analysis. 42,43 Even though non-Hispanic Black patients are less likely to undergo any type of treatment, including surgical treatment, for those who access surgical treatment they are no less likely to receive minimally invasive techniques. These findings may reflect the overall trend of increased uptake and availability of minimally invasive surgical technology in hospitals in metropolitan areas where the majority of non-Hispanic Black patients receive their care.…”
Section: Discussionmentioning
confidence: 99%
“…20,48 Area-level measures were primarily related to poverty status 19,37,42,47 or included in indices as composites with other variables (e.g., area deprivation index 34 or area-level poverty 19,42 ). Most studies examined disparities based on socioeconomic differences that were influenced by individual factors (n = 24), 19,20,27,30,34,37,42,45,47,48,50,[53][54][55][56]60,61,[63][64][65]67,70,71,74,75 built environment (n = 14), 19,30,37,42,47,48,53,54,56,61,63,64,71,75 and healthcare systems (n = 15). 20,…”
Section: Socioeconomic Status Disparities Among Older Adults With Cancermentioning
confidence: 99%
“…Most studies examined disparities based on socioeconomic differences that were influenced by individual factors (n = 24), 19,20,27,30,34,37,42,45,47,48,50,[53][54][55][56]60,61,[63][64][65]67,70,71,74,75 built environment (n = 14), 19,30,37,42,47,48,53,54,56,61,63,64,71,75 and healthcare systems (n = 15). 20,27,29,37,40,42,45,48,[54][55][56]60,…”
Section: Socioeconomic Status Disparities Among Older Adults With Cancermentioning
confidence: 99%
See 1 more Smart Citation